2017
DOI: 10.1016/j.ebiom.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Detection of IgE Reactivity to a Handful of Allergen Molecules in Early Childhood Predicts Respiratory Allergy in Adolescence

Abstract: BackgroundSensitization in early childhood may precede respiratory allergy in adolescence.MethodsIgE reactivity against 132 allergen molecules was evaluated using the MeDALL microarray in sera obtained from a random sample of 786 children at the age of 4, 8 and 16 years in a population based birth cohort (BAMSE). Symptoms were analyzed by questionnaire at ages 4, 8 and 16 years. Clinically and independent relevant allergen molecules accounting for ≥ 90% of IgE reactivities in sensitized individuals and at all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
94
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 40 publications
(48 reference statements)
10
94
0
Order By: Relevance
“…sIgE to Bet v 1 is a well‐known qualitative and quantitative marker of OAS . In the Swedish BAMSE cohort study, Bet v 1 was identified as a risk molecule, and as the most prevalent PR‐10 protein, with higher amount of specific IgE . The sensitization to this molecule in early childhood was associated with severe allergic rhinitis to birch pollen at 16 years of age and with OAS .…”
Section: Discussionmentioning
confidence: 99%
“…sIgE to Bet v 1 is a well‐known qualitative and quantitative marker of OAS . In the Swedish BAMSE cohort study, Bet v 1 was identified as a risk molecule, and as the most prevalent PR‐10 protein, with higher amount of specific IgE . The sensitization to this molecule in early childhood was associated with severe allergic rhinitis to birch pollen at 16 years of age and with OAS .…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these observations support the hypothesis that the skin is a key sensitizing organ both for food and for inhalant allergens that contribute to atopic disease progression. 5 Sensitizations to the latter were less prominent in our cohort, which may reflect regional differences in environmental exposures. Both ED visits and OCS courses were associated with sensitizations to seed storage proteins from peanut and We also observed co-sensitization between allergens of related protein families from different sources, such as for peanut and soy ( Figure S2 ).…”
mentioning
confidence: 67%
“…In contrast to other environmental allergens, the association with atopic dermatitis was present for Fel d 1, which may suggest that the skin is an important route of sensitization for this allergen. 5 Sensitizations identified to these allergens as early as 3-4 years old were useful for predicting development of respiratory allergy and asthma up to 16 years of age, in conjunction with environmental allergens from birch, grass, and dust mite. 3,4 To better understand sensitization profiles, component-resolved analysis was performed.…”
mentioning
confidence: 99%
“…From epidemiological investigations and birth cohort studies, we know that the development of asthma is preceded by early sensitization followed by clinical symptoms [106][107], often rhinitis, during childhood and may be predicted by measuring IgE reactivity to few allergen molecules [108]. As asthma has early origins and there are differences in its pre-/early-school forms [109], it is crucial to identify biomarkers of IgE sensitization before the clinical manifestation.…”
Section: Ige Specific For Certain Allergen Molecules or Combinations mentioning
confidence: 99%
“…Another important result from recently conducted birth cohort studies is that it seems to be possible to predict the development of allergic respiratory diseases according to "clinically silent" IgE reactivity profiles measured early in the life of children (Fig. 2), which opens possibilities for the prevention of asthma before the onset of symptoms [108,157,158]. Since respiratory allergy and asthma severely affect the life of children, one may consider to initiating preventive medical examinations (i.e., "allergy passport") based on determination of IgE reactivity profiles early in childhood to identify children who may benefit from preventive measures (Fig.…”
Section: Outdoor Allergens and Pediatric Asthmamentioning
confidence: 99%